Performance of two interferon-gamma release assays for tuberculosis infection screening in Kawasaki children before immunosuppressive therapy - Chen, Hao; Zheng, Huiwen; Cui, Lang; Xiao, Jing; Li, Feina; Wang, Yonghong; Guo, Yajie; Chen, Yuying; Yuan, Yue; Shen, Chen (Frontiers in Pediatrics, 2023)
Kawasaki disease (KD) is an acute systemic vasculitis of young children with unknown etiology. Identify mycobacterium tuberculosis (Mtb) infected KD patients by interferon-gamma release assays (IGRAs) before immunosuppressive therapy with glucocorticoids, tumour necrosis factor (TNF)-alpha inhibitors, and others were highly recommended , as these therapy would increase the risk of active tuberculosis (TB) disease in latently Mtb infected individuals. Here we evaluated the performance of the two common used by interferon-gamma release assays (IGRAs), ELISA-based QFT-GIT and ELISPOT-based X.DOT-TB tests, for identification of Mtb infection in KD children, and analyzed the associate factors effecting the test results by conducing a retrospective study on children with KD who were screened for Mtb infection by either two IGRAs at admission and hospitalized in Beijing Children's Hospital from July 2019 to April 2022. A total of 1327 cases were included. Among them, 932 cases were tested by QFT-GIT and 395 cases by X.DOT-TB. The positive rate of children was 0.1% and 0.2% by QFT-GIT and X.DOT-TB respectively, and the indeterminate rate was 68.2% and 6.1%. Patients with hypoproteinemia had a higher risk of getting an indeterminate X.DOT-TB result, and female, with critical ill, shock or hypoproteinemia presented statistically significant associations with an increased risk of obtaining an indeterminate QFT-GIT result. IVIG, as one commonly used key first-line KD therapeutic drug, could inhibited mitogen stimulated IFN-γ release directly with a high-dose inhibition by more than 90%, that might account for the high indeterminate incidence. In conclusion, X.DOT-TB could be more suitable than QFT-GIT for Mtb infection screening in children with KD.